Of what is "minimal cognition" the half-baked version?. (December 2020) - Lyon, Pamela
"Minimal cognition" is used in certain sectors of the cognitive sciences to make a kind of ontological claim that may be unique in the biological sciences: that a function operating in organisms living today is not a fully fledged version of that function (the nature of which remains unspecified), but, rather, exhibits the minimal requirements for whatever it is, properly conceived. Evidence suggests that elsewhere in the life sciences, deployment of minimizing qualifiers relative to a biological function appears largely restricted to two scenarios: first, attenuated functioning and, second, evolution of the function, real or synthetic. The article argues that "minimal cognition" and "proto-cognitive" were introduced at the turn of this century by cognitive researchers seeking to learn directly from evolved behavior, ecology and physiology. A terminological straitjacket imposed on the central object of cognitive science at its beginning necessitated the move. An alternative terminology is proposed, based on a phyletically neutral definition of cognition as a biological function; a candidate mechanism is explored; and a bacterial example presented. On this story, cognition is like respiration: ubiquitously present, from unicellular life to blue whales and every form of life in between, and for similar reasons: staying alive requires it.